Research Progress of Grating-Based X-Ray Phase-Contrast Imaging and Key Devices - Fangke Zong; Jun Yang; Jinchuan Guo; Jingjin Zhang; Yang Du; Chenggong Zhang (Photonics)
X-ray phase-contrast imaging presents a significant advancement in the field of X-ray imaging, surpassing traditional X-ray absorption imaging in detecting hydrogen substances. It effectively addresses the limitations of the latter in providing contrast for imaging weakly absorbing objects, thereby opening up vast potential applications in biomedical research, materials science, and industrial inspection. This article initially explores the fundamental principles of X-ray phase-contrast imaging and several prevalent imaging techniques. Notably, imaging devices such as grating-based Talbot–Lau interferometers emerge as the most promising in phase-contrast imaging due to their exceptional compatibility and imaging quality. Furthermore, this article introduces key parameters for assessing the quality of grating phase-contrast imaging, specifically image noise and sensitivity, along with their calculation methods. These insights are valuable for optimizing grating-based phase-contrast imaging devices. Lastly, this article examines potential applications and advancements in the key components of X-ray phase-contrast imaging while addressing current challenges and future directions in its technological development. This article aims to provide insights and inspiration for scholars interested in this field.